2009
DOI: 10.1039/b909610h
|View full text |Cite
|
Sign up to set email alerts
|

Low pressure CO2 to dimethyl carbonate by the reaction with methanol promoted by acetonitrile hydration

Abstract: CeO(2) catalysts catalyze the reaction of methanol with low pressure CO(2) to form dimethyl carbonate and the reaction was promoted by the combination with acetonitrile hydration over CeO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 25 publications
2
65
0
Order By: Relevance
“…[20][21][22][23][24][25][26] Cu/La 2 O 3 basic sites have as ignificant effect on the conversion to glycerol carbonate. [24] Liu et al synthesized CeO 2 with different morphologies using three methods:t raditional precipitation, hydrothermal synthesis and sol-gel citrate.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Cu/La 2 O 3 basic sites have as ignificant effect on the conversion to glycerol carbonate. [24] Liu et al synthesized CeO 2 with different morphologies using three methods:t raditional precipitation, hydrothermal synthesis and sol-gel citrate.…”
Section: Introductionmentioning
confidence: 99%
“…Honda et al [124,125] reported carbonylation of methanol using acetonitrile as dehydrating agent instead of a ketal. They reached a DMC yield of 3 % at 0.…”
Section: Dehydrating Agentsmentioning
confidence: 98%
“…The effect of the addition of acetonitrile to the DMC synthesis over ceria was investigated [46]. The hydration of acetonitrile produces acetamide (Eq.…”
Section: Use Of Acetonitrile As a Dehydrating Agent For Dmc Synthesismentioning
confidence: 99%
“…The use of 2,2-dimethoxypropane as a dehydrating agent was applied to ceria-based catalysts [46]. However, this approach was less effective for DMC synthesis over ceria (CeO 2 -HS calcined at 873 K) than the use of nitriles.…”
Section: Use Of Other Dehydrating Agentsmentioning
confidence: 99%
See 1 more Smart Citation